Functional magnetic composite microsphere, preparation method and application thereof, and method for removing noble metal catalyst in hydrogenated butadiene-acrylonitrile rubber solution
Through the magnetic nanoparticle coating and functional group grafting technology of functional magnetic composite microspheres, the problem of difficult separation of precious metal catalysts in hydrogenated nitrile rubber rubber liquid is solved, and efficient and pollution-free catalyst separation effect is achieved.
Patent Information
- Application Number
- CN202310706208.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-17
AI Technical Summary
The prior art is difficult to efficiently separate precious metal catalysts from hydrogenated nitrile rubber rubber solution, resulting in catalyst residue affecting product aging performance, and the existing methods have problems of contamination and limited scope of application.
Functional magnetic composite microspheres were used to coat magnetic nanoparticles and graft functional groups on the SiO2 coating layer, adsorb and separate the noble metal catalyst from the hydrogenated nitrile rubber rubber solution through magnetic separation.
It realizes efficient separation of precious metal catalysts and is suitable for high-concentration hydrogenated nitrile rubber rubber solution, avoids contamination of products and improves removal rate.
Smart Images

Figure BDA0004286258030000121 
Figure BDA0004286258030000131 
Figure BDA0004286258030000141
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalyst separation, and in particular to a functional magnetic composite microsphere, a preparation method and application thereof, and a method for removing noble metal catalysts from hydrogenated nitrile rubber solution. Background Art
[0002] Hydrogenated nitrile rubber has good properties such as wear resistance, low temperature resistance (-40℃), oxidation resistance, ozone resistance and thermal stability. It can be used to manufacture parts of automobile fuel systems, oil field blowout preventers, seals of nuclear power plants and printing and dyeing rubber rollers. It is currently mainly made by hydrogenation modification of nitrile rubber. At present, most hydrogenated nitrile products on the market are produced by solution hydrogenation. The hydrogenation process generally uses precious metal catalysts. Precious metal catalysts are mainly composed of precious metals and one or more organic ligands. The catalyst is dispersed in the polymer solution in molecular form, and it is difficult to separate the catalyst from the polymer. If the catalyst remains in the hydrogenated nitrile rubber product, it will seriously affect its aging performance.
[0003] Currently, the methods for separating the catalyst from the polymer solution are:
[0004] (1) The precious metal catalyst in hydrogenated nitrile rubber is precipitated by adding organic additives such as thiourea and polysaccharides. If these organic additives cannot be completely separated from the hydrogenated nitrile rubber solution, they will cause secondary pollution to the product.
[0005] (2) Using a complexing agent and an extractant in sequence to convert the precious metal catalyst remaining in the unsaturated copolymer solution into a metal organic complex soluble in the aqueous extractant solution. This method cannot completely remove the precious metal catalyst, and the complexing agent may become a new pollutant.
[0006] (3) Use functionalized chelating resin to adsorb precious metals in hydrogenated nitrile rubber solution. However, this method is only applicable to low-viscosity solutions, otherwise the pores of the chelating resin will be blocked and the adsorption effect cannot be achieved. Summary of the invention
[0007] The purpose of the present invention is to overcome the problems of catalyst separation difficulties and low catalyst removal rate in the prior art, and to provide a functional magnetic composite microsphere and its preparation method and application, and a method for removing precious metal catalysts from hydrogenated nitrile rubber glue. The functional magnetic composite microsphere uses the functional groups on its surface to adsorb the precious metal catalysts in the hydrogenated nitrile rubber glue, and then separates the microspheres from the glue by magnetic separation, thereby achieving efficient separation of the precious metal catalysts.
[0008] In order to achieve the above object, the present invention provides a functional magnetic composite microsphere in the first aspect, characterized in that the functional magnetic composite microsphere comprises magnetic nanoparticles and SiO2 coated on the surface of the magnetic nanoparticles. 2 cladding;
[0009] Among them, in the SiO 2 The surface of the coating layer is grafted with functional groups;
[0010] Based on the weight of the functional magnetic composite microspheres, the content of the functional groups is 0.01-5 mmol / g;
[0011] The functional magnetic composite microspheres are used for removing metal catalysts from hydrogenated nitrile rubber solution.
[0012] The second aspect of the present invention provides a method for preparing functional magnetic composite microspheres, characterized in that the method comprises:
[0013] S1, coating the magnetic nanoparticles with a coating agent to obtain magnetic composite microspheres;
[0014] S2, reacting the magnetic composite microspheres, coupling agent and functional compound in the presence of a solvent to obtain functional magnetic composite microspheres;
[0015] The molar ratio of the magnetic composite nanoparticles calculated based on silicon dioxide, the coupling agent and the functional compound calculated based on the functional group is 1:0.02-0.2:0.1-1.
[0016] The third aspect of the present invention provides a functional magnetic composite microsphere prepared by the preparation method provided by the second aspect of the present invention.
[0017] A fourth aspect of the present invention provides an application of the functional magnetic composite microspheres in removing precious metal catalysts from hydrogenated nitrile rubber solution.
[0018] A fifth aspect of the present invention provides a method for removing precious metal catalysts from hydrogenated nitrile rubber solution, characterized in that the method comprises: contacting functional magnetic composite microspheres with hydrogenated nitrile rubber solution to obtain precious metal catalysts by magnetic separation;
[0019] Wherein, the content of hydrogenated nitrile rubber in the hydrogenated nitrile rubber solution is 0.5-20wt%;
[0020] The hydrogenated nitrile rubber liquid comes from the hydrogenation reaction of nitrile rubber;
[0021] The functional magnetic composite microspheres are the functional magnetic composite microspheres mentioned above.
[0022] Through the above technical scheme, the functional magnetic composite microspheres and their preparation method and application, and the method for removing precious metal catalysts from hydrogenated nitrile rubber liquid provided by the present invention achieve the following beneficial effects: the functional magnetic composite microspheres can efficiently separate the precious metal catalysts from the hydrogenated nitrile rubber liquid by adsorbing the precious metal catalysts in the hydrogenated nitrile rubber liquid without polluting the hydrogenated nitrile rubber liquid, and the method is suitable for hydrogenated nitrile rubber liquid with higher concentration. DETAILED DESCRIPTION
[0023] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0024] The first aspect of the present invention provides a functional magnetic composite microsphere, characterized in that the functional magnetic composite microsphere comprises magnetic nanoparticles and SiO2 coated on the surface of the magnetic nanoparticles. 2 cladding;
[0025] The surface of the coating layer is grafted with functional groups;
[0026] Based on the weight of the functional magnetic composite microspheres, the content of the functional groups is 0.01-5 mmol / g;
[0027] The functional magnetic composite microspheres are used for removing metal catalysts from hydrogenated nitrile rubber solution.
[0028] In the present invention, the functional magnetic composite microspheres coat the base magnetic nanoparticles through the coating layer, which can prevent the aggregation of the magnetic nanoparticles, protect the magnetism of the magnetic nanoparticles, and facilitate further modification and functionalization thereof.
[0029] Furthermore, the coating layer surface of the functional magnetic composite microsphere contains a specific content of functional groups, and when used, the noble metal catalyst in the hydrogenated nitrile rubber solution is adsorbed to achieve efficient magnetic separation of the noble metal catalyst.
[0030] According to the present invention, the content of the functional group is 0.1-3 mmol / g;
[0031] According to the present invention, the saturation magnetization intensity of the functional magnetic composite microspheres is 5-30emu / g, preferably 20-30emu / g.
[0032] According to the present invention, the average particle size of the functional magnetic composite microspheres is 30-400 nm.
[0033] In the present invention, the average particle size of the functional magnetic composite microspheres meets the above range, which can avoid agglomeration and ensure the removal efficiency of the precious metal catalyst.
[0034] According to the present invention, the SiO 2 The thickness of the coating layer is 5-380 nm, preferably 9-250 nm.
[0035] According to the present invention, the average particle size of the magnetic nanoparticles is 5-50 nm, and the saturation magnetization is 5-50 emu / g.
[0036] In the present invention, if either the average particle size or the saturation magnetization of the magnetic nanoparticles satisfies the above range, the removal rate of the noble metal catalyst can be higher.
[0037] Furthermore, the average particle size of the magnetic nanoparticles is 10-30 nm, and the saturation magnetization is 25-50 emu / g.
[0038] According to the present invention, the magnetic nanoparticles are selected from Fe 3 O 4 At least one of Fe nanoparticles, Fe nanoparticles and Co nanoparticles.
[0039] According to the present invention, the functional group is selected from at least one of an amino group, a thiol group, a thiourea group, a carboxyl group, an ester group, a hydroxyl group, a carbonyl group, an amide group, a phosphate group and an ether group.
[0040] In the present invention, the type of the functional group satisfies the above range, can be adsorbed by the noble metal catalyst through complex reaction, will not cause pollution to the hydrogenated nitrile rubber solution, and because it can improve the adsorption of the noble metal catalyst, thereby improving the removal rate of the noble metal catalyst.
[0041] The second aspect of the present invention provides a method for preparing functional magnetic composite microspheres, characterized in that the method comprises:
[0042] S1, coating the magnetic nanoparticles with a coating agent to obtain magnetic composite microspheres;
[0043] S2, reacting the magnetic composite microspheres, coupling agent and functional compound in the presence of a solvent to obtain functional magnetic composite microspheres;
[0044] The molar ratio of the magnetic composite nanoparticles calculated based on silicon dioxide, the coupling agent and the functional compound calculated based on the functional group is 1:0.02-0.2:0.1-1.
[0045] In the present invention, the functional magnetic composite microspheres contain magnetic nanoparticles, and the magnetic nanoparticles are coated with a coating layer, so that the magnetic nanoparticles are not easy to agglomerate.
[0046] According to the present invention, the magnetic nanoparticles are prepared by at least one of a chemical coprecipitation method, a hydrothermal method, a solvothermal method, a microemulsion method and a sol-gel method.
[0047] In the present invention, in order to obtain better technical effects, the magnetic nanoparticles are prepared according to the following method:
[0048] In the present invention, the magnetic nanoparticles are prepared by the following method:
[0049] a. FeCl 3 6H 2 O is dissolved in ethylene glycol, sodium acetate and polyethylene glycol are added, stirred evenly, and then placed at 180-220°C for 15-25h (where FeCl 3 6H 2 O, sodium acetate and polyethylene glycol (mass ratio is 1:2.4-4.5:0.4-1.1) to obtain a solid;
[0050] b. The obtained solid was washed with deionized water and ethanol to obtain Fe 3 O 4 The nanoparticles are dispersed in a solvent for later use.
[0051] In the present invention, in order to achieve better technical effects, the magnetic nanoparticles are preferably added in the form of a dispersion. There is no particular limitation on the solvent in the dispersion. In order to facilitate the subsequent coating of the magnetic nanoparticles, the solvent is preferably an alcohol solvent, such as ethanol, ethylene glycol, etc.
[0052] In the present invention, the content of the magnetic nanoparticles in the dispersion is 0.005-0.02 g / ml.
[0053] According to the present invention, the coating is selected from at least one of a sol-gel method, a reverse microemulsion method, an aerosol high-temperature decomposition method, an ultrasonic synthesis method and a template method.
[0054] In the present invention, in order to make the average particle size of the generated functional composite magnetic microspheres suitable and further improve the removal rate of the noble metal catalyst, it is preferred to select a sol-gel method for coating.
[0055] According to the present invention, the coating is performed by the following method: dispersing magnetic nanoparticles in alcohol to generate a magnetic nanoparticle dispersion, adding a coating agent and deionized water in the presence of an alkaline substance to react to obtain magnetic composite microspheres.
[0056] According to the present invention, the volume ratio of the magnetic nanoparticle dispersion: coating agent: alkaline substance: deionized water is 1: 0.01-0.5: 0.02-4: 0.2-3.
[0057] In the present invention, when the volume ratio of the magnetic nanoparticle dispersion, the coating agent, the alkaline substance and the deionized water meets the above range, magnetic composite microspheres with a suitable particle size can be obtained.
[0058] According to the present invention, the volume ratio of the magnetic nanoparticle dispersion: coating agent: alkaline substance: deionized water is 1:0.05-0.2:0.5-2:1-2.
[0059] According to the present invention, the coating agent is selected from ethyl orthosilicate and / or methyl orthosilicate.
[0060] According to the present invention, the magnetic nanoparticles are selected from Fe 3 O 4 At least one of nanoparticles, Fe nanoparticles, and Co nanoparticles.
[0061] In the present invention, the alkaline substance is selected from at least one of aqueous ammonia, sodium hydroxide and potassium hydroxide, preferably aqueous ammonia.
[0062] In the present invention, the alkaline substance is preferably concentrated ammonia water with a mass fraction of 27 wt%.
[0063] The functional compound is selected from compounds containing at least one functional group selected from the group consisting of amino, thiol, thiourea, carboxyl, ester, hydroxyl, carbonyl, amide, phosphoric acid and ether.
[0064] In the present invention, the method further comprises washing and drying the obtained product after coating the magnetic composite nanoparticles.
[0065] In the present invention, there is no particular limitation on the washing and drying conditions, and the washing and drying conditions may be conventional washing and drying methods in the art.
[0066] In the present invention, in step S2, preferably a stepwise reaction is used. Specifically, the magnetic composite microspheres and the coupling agent are first subjected to a first reaction to obtain coupled magnetic composite microspheres, and then the coupled magnetic composite microspheres and the functional compound are subjected to a second reaction in the presence of NaH to obtain functional magnetic composite microspheres.
[0067] In the present invention, the molar ratio of the magnetic composite nanoparticles to the coupling agent is 1:0.02-0.2 based on silicon dioxide.
[0068] In the present invention, the molar ratio of the magnetic composite microspheres calculated as silicon dioxide, the functional compound calculated as functional groups and NaH is 1:0.1-1:0.1-2.
[0069] In the present invention, the conditions of the first reaction include: temperature 120-160° C., time 30-60 h.
[0070] In the present invention, the conditions of the second reaction include: temperature 70-100° C., time 30-60 h.
[0071] In the present invention, the first reaction and the second reaction are preferably carried out in an organic solvent, for example, the organic solvent may be toluene and / or N,N-dimethylformamide.
[0072] In the present invention, the coupling agent is not particularly limited, and may be, for example, chloropropyltriethoxysilane.
[0073] The third aspect of the present invention provides a functional magnetic composite microsphere prepared by the preparation method provided by the second aspect of the present invention.
[0074] The fourth aspect of the present invention provides an application of the functional magnetic composite microspheres described in the third aspect in removing precious metal catalysts from hydrogenated nitrile rubber liquid.
[0075] A fifth aspect of the present invention provides a method for removing precious metal catalysts from hydrogenated nitrile rubber solution, characterized in that the method comprises: contacting functional magnetic composite microspheres with hydrogenated nitrile rubber solution to obtain precious metal catalysts by magnetic separation;
[0076] Wherein, the content of hydrogenated nitrile rubber in the hydrogenated nitrile rubber solution is 0.5-20wt%;
[0077] The hydrogenated nitrile rubber liquid comes from the hydrogenation reaction of nitrile rubber;
[0078] The functional magnetic composite microspheres are the functional magnetic composite microspheres described in the first aspect and / or the third aspect of the present invention.
[0079] In the present invention, when the content of hydrogenated nitrile rubber in the hydrogenated nitrile rubber solution meets the above range, the viscosity of the solution is beneficial to improving the removal rate of the precious metal catalyst.
[0080] In the present invention, the conditions for the hydrogenation reaction of the nitrile rubber are not particularly limited, and can be conventional conditions in the art, for example, carried out according to the following method:
[0081] Under nitrogen protection, nitrile rubber is dissolved in an organic solvent in proportion, a noble metal catalyst is added thereto, the mixture is heated to 60-150°C, and the mixture is reacted for 2-24 hours under a hydrogen pressure of 3-10 MPa, and then the temperature and pressure are reduced to obtain a hydrogenated nitrile rubber solution.
[0082] According to the present invention, the hydrogenated nitrile rubber solution contains hydrogenated nitrile rubber and a noble metal catalyst.
[0083] Furthermore, the hydrogenated nitrile rubber solution also contains an organic solvent, and the organic solvent is selected from at least one of aromatic hydrocarbons, derivatives of aromatic hydrocarbons substituted by alkyl or halogen, halogenated alkanes, ethers, ketones and amides.
[0084] Furthermore, the organic solvent is at least one of benzene, toluene, xylene, chlorobenzene, dichlorobenzene, trichlorobenzene, dichloromethane, chloroform, 1,2-dichloroethane, tetrahydrofuran, acetone, butanone and N,N-dimethylformamide.
[0085] In the present invention, the content of hydrogenated nitrile rubber in the hydrogenated nitrile rubber solution is 0.5-12wt%.
[0086] According to the present invention, in the hydrogenated nitrile rubber solution, the content of the noble metal catalyst is 30-170 ppm of the hydrogenated nitrile rubber in terms of noble metal.
[0087] In the present invention, the content of the noble metal catalyst meets the above range, can meet the hydrogenation degree of the nitrile rubber, and can further react with the functional magnetic composite microspheres, thereby improving the removal rate of the noble metal catalyst.
[0088] Furthermore, in the hydrogenated nitrile rubber solution, the content of the noble metal catalyst is 40-110 ppm of the hydrogenated nitrile rubber in terms of noble metal.
[0089] According to the present invention, the noble metal catalyst has the general formula shown in Formula I and / or Formula II:
[0090] M p X m L n Formula I;
[0091] M 1 a M 2 b X c L d Formula II;
[0092] Wherein, in formula I, M is selected from one of the noble metals of Group VIII; X is selected from at least one of chlorine, bromine and hydrogen; L is selected from at least one of organic phosphine, organic diphosphine, organic cerium compound, nitrogen-containing organic compound, sulfur-containing organic compound and oxygen-containing organic compound; p is an integer of 1-6, m is an integer of 1-7, and n is an integer of 3-21.
[0093] Further, in Formula I, M is selected from rhodium, ruthenium or palladium; X is chlorine;
[0094] According to the present invention, in Formula II, M 1 and M2 are each independently selected from one of the noble metals of Group VIII, and M 1 and M 2 are not the same; L is selected from at least one of an organic phosphine, an organic bisphosphine, an organic cerium compound, a nitrogen-containing organic compound, a sulfur-containing organic compound or an oxygen-containing organic compound; a is an integer of 1-6, b is an integer of 1-3, c is an integer of 1-7, and d is an integer of 3-21.
[0095] In the present invention, the type of the noble metal catalyst meets the above range, can meet the requirements of the hydrogenation degree of nitrile rubber, and can undergo complexation reaction with the functional groups on the surface of the functional magnetic composite microspheres to be adsorbed and separated.
[0096] In the present invention, there is no particular limitation on the preparation method of the noble metal catalyst, as long as the noble metal catalyst has the composition shown in the above general formula. For example, it can be prepared according to the following method:
[0097] a. dissolving at least one of an organic phosphine, an organic bisphosphine, an organic cerium compound, a nitrogen-containing organic compound, a sulfur-containing organic compound and an oxygen-containing organic compound in a first solvent at 55-80° C. under argon protection to obtain a mixed solution;
[0098] b. Dissolve the noble metal salt in the second solvent under argon protection, heat to reflux, and dropwise add it into the above mixed solution to react for 2-3 hours, cool to 20-30° C., separate and wash the product to obtain the noble metal catalyst.
[0099] In the present invention, the types of the first solvent and the second solvent are not particularly limited, and they may be conventional solvents in the art, such as ethanol, n-propanol, n-butanol, and the like.
[0100] In the present invention, the separation is not particularly limited, and may be, for example, suction filtration, centrifugal filtration, etc.
[0101] In the present invention, the washing is not particularly limited, and for example, ether can be used for washing 2-3 times.
[0102] According to the present invention, the mass ratio of the functional magnetic composite microspheres to the hydrogenated nitrile rubber solution is 1:1-190.
[0103] In the present invention, the volume ratio of the hydrogenated nitrile rubber solution to the functional magnetic composite microspheres satisfies the above range, which can improve the removal rate of the noble metal catalyst.
[0104] According to the present invention, the mass ratio of the functional magnetic composite microspheres to the hydrogenated nitrile rubber solution is 1:3-150.
[0105] According to the present invention, the contacting conditions include: temperature of 40-120° C., preferably 60-120° C.; time of 2-48 h, preferably 4-24 h.
[0106] In the present invention, the contact conditions satisfy the above range, which enables the functional magnetic composite microspheres to fully contact with the noble metal catalyst in the hydrogenated nitrile rubber solution, thereby further improving the removal rate of the noble metal catalyst.
[0107] According to the present invention, the magnetic separation conditions are not particularly limited, such as separating the functional magnetic composite microspheres from the colloid under the action of an external magnetic field.
[0108] In the present invention, there is no particular limitation on the magnetic field strength of the external magnetic field, and it can be selected as needed.
[0109] The present invention will be described in detail below by way of examples. In the following examples,
[0110] The removal rate of the precious metal catalyst is calculated by the following formula:
[0111] Removal rate = (mass of rhodium metal in the glue solution before removal - mass of rhodium metal in the glue solution after removal) / mass of rhodium metal in the glue solution before removal;
[0112] The content of noble metal catalysts was measured by ICP-OES inductively coupled plasma atomic emission spectrometry;
[0113] The saturation magnetization was measured by a vibrating sample magnetometer (model 7307) from Lake Shore, USA;
[0114] Nitrile rubber, purchased from PetroChina Lanzhou Petrochemical Company, brand 4105;
[0115] NaH, 60 wt%, dispersed in mineral oil;
[0116] Other raw materials were commercially available analytical grade drugs.
[0117] The magnetic nanoparticles used in the present invention are prepared by the following method
[0118] a. Add 70g FeCl 3 6H 2 O was dissolved in 1L ethylene glycol, and 178g sodium acetate and 49g polyethylene glycol were added, among which FeCl 3 6H 2 The mass ratio of O, sodium acetate and polyethylene glycol is 1:2.5:0.7. After stirring evenly, place at 200°C for reaction for 20 hours, and filter to obtain a solid;
[0119] b. Wash the obtained solid with deionized water and ethanol to obtain Fe3 O 4 Nanoparticles with an average particle size of 13 nm and a saturation magnetization of 28 emu / g were dispersed in ethanol to obtain Fe 3 O 4 Dispersion (Fe 3 O 4 The content is 1wt%).
[0120] The following preparation example is used to describe the preparation of magnetic composite microspheres.
[0121] Preparation Example 1
[0122] The 100 mL Fe 3 O 4 The dispersion was stirred and mixed evenly with 5.5 mL of tetraethyl orthosilicate, 50 mL of concentrated ammonia water (27 wt%) and 150 mL of deionized water, and then sealed for reaction for 4 hours. The obtained product was fully washed with deionized water and ethanol to obtain magnetic composite microspheres Y-1, whose average particle size, coating layer thickness and saturation magnetization are shown in Table 1.
[0123] Preparation Example 2
[0124] The method is consistent with that of Preparation Example 1, except that the amount of concentrated ammonia water (27 wt %) used is 80 mL. Finally, magnetic composite microspheres Y-2 are obtained, and their average particle size, coating layer thickness and saturation magnetization are shown in Table 1.
[0125] Preparation Example 3
[0126] The method is consistent with that of Preparation Example 1, except that the amount of deionized water used is 100 mL. Finally, magnetic composite microspheres Y-3 are obtained, and their average particle size, coating layer thickness and saturation magnetization are shown in Table 1.
[0127] Preparation Example 4
[0128] The method is consistent with that of Preparation Example 1, except that the amount of concentrated ammonia water (27 wt %) used is 500 mL. Finally, magnetic composite microspheres Y-4 are obtained, and their average particle size, coating layer thickness and saturation magnetization are shown in Table 1.
[0129] Table 1
[0130]
[0131] The following preparation example is used to illustrate the preparation of functional magnetic composite microspheres
[0132] Preparation Example 5
[0133] In the presence of 100 mL of toluene, 10 g of the magnetic composite microspheres Y-1 prepared in Preparation Example 1 and 1 g of chloropropyltriethoxysilane were stirred and refluxed at 150° C. for 30 h and then centrifuged to obtain coupled magnetic composite microspheres, wherein the molar ratio of the magnetic composite nanoparticles to the coupling agent based on silicon dioxide was 1:0.03. The coupled magnetic composite microspheres were fully washed with ethanol and then dried in a vacuum drying oven at 90° C. for 6 h.
[0134] 10 g of coupled magnetic composite microspheres, 2 g of thiourea and NaH solution (containing 0.5 g of NaH) were added to 25 mL of N,N-dimethylformamide, stirred and refluxed at 80°C for 48 hours, and then centrifuged. The product was fully washed with ethanol and dried in a vacuum drying oven at 100°C for 12 hours to obtain functional magnetic composite microspheres, wherein the molar ratio of the magnetic composite microspheres calculated on the basis of silica, the functional compound calculated on the basis of functional groups, and NaH was 1:0.16:0.13.
[0135] The average particle size, surface functional group type and content, and saturation magnetization of A1 of the functional magnetic composite microspheres are shown in Table 2.
[0136] Preparation Example 6-8
[0137] The method is consistent with that of Preparation Example 5, except that the magnetic composite microsphere Y-1 prepared in Preparation Example 1 is replaced by the magnetic composite microspheres Y-2, Y-3 and Y-4 prepared in Preparation Examples 2-4 to obtain functional magnetic composite microspheres A2-A4;
[0138] The average particle size, surface functional group type and content, and saturation magnetization intensity of A2-A4 of the functional magnetic composite microspheres are shown in Table 2.
[0139] Preparation Example 9
[0140] The method is consistent with that of Preparation Example 5, except that thiourea is replaced by aniline.
[0141] The average particle size, surface functional group type and content, and saturation magnetization of the obtained functional magnetic composite microspheres A5 are shown in Table 2.
[0142] Preparation Example 10
[0143] The method is consistent with that of Preparation Example 5, except that thiourea is replaced by pentamethylenethiol.
[0144] The average particle size, surface functional group type and content, and saturation magnetization intensity of the obtained functional magnetic composite microspheres A6 are shown in Table 2.
[0145] Comparative Preparation Example 1
[0146] The method is consistent with that of Preparation Example 5, except that the amount of thiourea used is 0.6 g, so that the molar ratio of the magnetic composite nanoparticles and the functional compound calculated on the basis of silicon dioxide is 1:0.05.
[0147] The average particle size, surface functional group type and content, and saturation magnetization of the obtained functional magnetic composite microspheres D1 are shown in Table 2.
[0148] Table 2
[0149]
[0150]
[0151] The following preparation examples are used to illustrate the preparation of precious metal catalysts.
[0152] Preparation Example 11
[0153] a. 4.5 g PPh 3 Dissolve in 70°C hot ethanol solution under argon protection to obtain a mixed solution, and add it to the reaction bottle;
[0154] b. Weigh 0.75 g RhCl 3 ·H 2 O was dissolved in ethanol solution under argon protection and heated under reflux at 78 °C to remove RhCl 3 ·H 2 O ethanol solution was added dropwise to the reaction flask for 2.5 hours, cooled to 25°C, filtered, and washed with ether to obtain the noble metal catalyst [(C 6 H 5 ) 3 P] 3 RhCl, named cat-1, wherein M is rhodium, X is chlorine, L is triphenylphosphine, p is 1, m is 1, and n is 3.
[0155] Preparation Example 12
[0156] a. 4.5 g PPh 3 Dissolve in 70°C hot ethanol solution under argon protection to obtain a mixed solution, and add it to the reaction bottle;
[0157] b. Weigh 0.75 g RhCl 3 ·H 2 O was dissolved in ethanol solution under argon protection and heated under reflux at 78 °C to 3 ·H 2 O ethanol solution was added dropwise to the reaction flask for 2.5 hours, cooled to 25°C, filtered, and washed with ether to obtain a powdered hydrogenation catalyst [(C 6 H 5 ) 3P] 3 RuCl, named cat-2, where M is ruthenium, X is chlorine, L is triphenylphosphine, p is 1, m is 2, and n is 3.
[0158] Preparation Example 13
[0159] Cat-3 was prepared by mixing 1 part of cat-1 and 0.5 parts of cat-2, wherein the molar ratio of Rh to Ru was 2:1.
[0160] The following examples are used to illustrate the application of the above-mentioned functional magnetic composite microspheres in the removal of precious metal catalysts from hydrogenated nitrile rubber solution.
[0161] Preparation Example 14
[0162] Under nitrogen protection, 54 g of nitrile rubber was dissolved in 546 g of chlorobenzene solution, 48.47 mg of the noble metal catalyst cat1 was added, the temperature was raised to 110°C, and the reaction was carried out for 6 hours under a hydrogen pressure of 6 MPa. The temperature and pressure were then lowered to obtain a hydrogenated nitrile rubber solution for later use (the degree of hydrogenation was measured to be 88%).
[0163] The amounts of nitrile rubber and chlorobenzene, the types of precious metal catalysts, the amounts of precious metal catalysts added, the reaction temperatures, the reaction pressures, the reaction times and the degree of hydrogenation in Preparation Examples 14-19 and Comparative Preparation Example 2 are listed in Table 3.
[0164] Table 3
[0165]
[0166] Examples 1-15, Comparative Examples 1-2
[0167] Types of hydrogenated nitrile rubber liquid and content of hydrogenated nitrile rubber a (the proportion of the mass of hydrogenated nitrile rubber in the sum of the mass of hydrogenated nitrile rubber and organic solvent), precious metal content (the mass of precious metal relative to the mass content of hydrogenated nitrile rubber), type of precious metal catalyst in the glue solution, type of functional groups on the surface of functional magnetic composite microspheres, saturation magnetization intensity and addition ratio (i.e. the mass ratio of functional magnetic composite microspheres and hydrogenated nitrile rubber glue solution), removal temperature and removal time are shown in Table 4, and the catalyst removal rate is shown in Table 5.
[0168] Table 4
[0169]
[0170] Comparative Example 3
[0171] The method is consistent with Example 1, except that a macroporous chelating resin with thiourea groups (XSC-600, purchased from Xi'an Woze Environmental Protection Technology Co., Ltd.) is used to remove the catalyst in the glue solution.
[0172] Table 5
[0173]
[0174]
[0175] It can be seen from the above results that the embodiments provided by the present invention have a good effect of removing precious metal catalysts, and the removal rate is above 70%. Among them, the removal rate of precious metal catalysts in the preferred embodiments reaches above 90%.
[0176] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A functional magnetic composite microsphere, It is characterized in that The functional magnetic composite microspheres include magnetic nanoparticles and SiO2 coated on the surface of the magnetic nanoparticles. 2 Cladding layer; Among them, in the SiO 2 The surface of the coating layer is grafted with functional groups; Based on the weight of the functional magnetic composite microspheres, the content of the functional groups is 0.01-5 mmol / g; The functional magnetic composite microspheres are used for removing metal catalysts from hydrogenated nitrile rubber solution.
2. The functional magnetic composite microsphere according to claim 1, in, The content of the functional group is 0.1-3mmol / g; Preferably, the saturation magnetization of the functional magnetic composite microspheres is 5-30emu / g, preferably 20-30emu / g; Preferably, the average particle size of the functional magnetic composite microspheres is 30-400 nm; Preferably, the SiO 2 The thickness of the coating layer is 5-380 nm, preferably 9-250 nm.
3. The functional magnetic composite microsphere according to claim 1 or 2, in, The average particle size of the magnetic nanoparticles is 5-50 nm, and the saturation magnetization is 5-50 emu / g; Preferably, the magnetic nanoparticles are selected from Fe 3 O 4 At least one of nanoparticles, Fe nanoparticles and Co nanoparticles; Preferably, the functional group is selected from at least one of an amino group, a thiol group, a thiourea group, a carboxyl group, an ester group, a hydroxyl group, a carbonyl group, an amide group, a phosphate group and an ether group.
4. A method for preparing functional magnetic composite microspheres, It is characterized in that The method comprises: S1, coating the magnetic nanoparticles with a coating agent to obtain magnetic composite microspheres; S2, reacting the magnetic composite microspheres, coupling agent, and functional compound in the presence of a solvent to obtain functional magnetic composite microspheres; The molar ratio of the magnetic composite nanoparticles calculated based on silicon dioxide, the coupling agent and the functional compound calculated based on the functional group is 1:0.02-0.2:0.1-1.
5. The preparation method according to claim 4, in, The magnetic nanoparticles are prepared by at least one of a chemical coprecipitation method, a hydrothermal method, a microemulsion method and a sol-gel method; Preferably, the coating is selected from at least one of a sol-gel method, a reverse microemulsion method, an aerosol high-temperature decomposition method, an ultrasonic synthesis method and a template method; Preferably, the coating is performed by the following method: dispersing magnetic nanoparticles in alcohol to generate a magnetic nanoparticle dispersion, adding a coating agent and deionized water in the presence of an alkaline substance to react to obtain magnetic composite microspheres; Preferably, the volume ratio of the magnetic nanoparticle dispersion: coating agent: alkaline substance: deionized water is 1:0.01-0.5:0.02-4:0.2-3, preferably 1:0.05-0.2:0.5-2:1-2.
6. The preparation method according to claim 4 or 5, in, The coating agent is selected from ethyl orthosilicate and / or methyl orthosilicate; Preferably, the magnetic nanoparticles are selected from Fe 3 O 4 At least one of nanoparticles, Fe nanoparticles and Co nanoparticles; Preferably, the functional compound is selected from compounds containing at least one functional group selected from the group consisting of amino, thiol, thiourea, carboxyl, ester, hydroxyl, carbonyl, amide, phosphate and ether.
7. Functional magnetic composite microspheres prepared by the preparation method according to any one of claims 4 to 6.
8. Use of the functional magnetic composite microspheres according to claim 7 in removing precious metal catalysts from hydrogenated nitrile rubber solution.
9. A method for removing precious metal catalysts from hydrogenated nitrile rubber solution, It is characterized in that The method comprises: contacting functional magnetic composite microspheres with hydrogenated nitrile rubber solution, and obtaining a noble metal catalyst by magnetic separation; Wherein, the content of hydrogenated nitrile rubber in the hydrogenated nitrile rubber solution is 0.5-20wt%; The hydrogenated nitrile rubber solution comes from the hydrogenation reaction of nitrile rubber; The functional magnetic composite microspheres are the functional magnetic composite microspheres described in any one of claims 1-3 and / or 7.
10. The method according to claim 9, in, The hydrogenated nitrile rubber solution contains hydrogenated nitrile rubber and a noble metal catalyst; Preferably, the content of hydrogenated nitrile rubber in the hydrogenated nitrile rubber solution is 0.5-12wt%; Preferably, in the hydrogenated nitrile rubber solution, the content of the noble metal catalyst is 30-170 ppm, preferably 40-110 ppm, of the hydrogenated nitrile rubber, calculated as noble metal.
11. The method according to claim 9 or 10, in, The noble metal catalyst has the general formula shown in Formula I and / or Formula II: M p X m L n Formula I; M 1 a M 2 b X c L d Formula II; Wherein, in Formula I, M is selected from one of the noble metals of Group VIII; X is selected from at least one of chlorine, bromine and hydrogen; L is selected from at least one of an organic phosphine, an organic diphosphine and a cerium-containing compound; p is an integer of 1-6, m is an integer of 1-7, and n is an integer of 3-21; Preferably, in Formula I, M is selected from rhodium, ruthenium or palladium; X is chlorine; the cerium-containing compound contains at least one element selected from nitrogen, sulfur and oxygen; Preferably, in Formula II, M 1 and M 2 are each independently selected from one of the noble metals of Group VIII, and M 1 and M 2 are not the same; L is selected from at least one of an organic phosphine compound, an organic bisphosphine compound, an organic cerium compound, a nitrogen-containing organic compound, a sulfur-containing organic compound or an oxygen-containing organic compound; a is an integer of 1-6, b is an integer of 1-3, c is an integer of 1-7, and d is an integer of 3-21.
12. The method according to any one of claims 9 to 11, in, The mass ratio of the functional magnetic composite microspheres to the hydrogenated nitrile rubber solution is 1:1-190, preferably 1:3-150; Preferably, the contacting conditions include: temperature of 40-120°C, preferably 60-120°C; time of 2-48h, preferably 4-24h.
Citation Information
Cited By
Recovery method of homogeneous catalyst for hydrogenated butadiene-acrylonitrile rubber synthesis
CN119972199A
A method for recovering a homogeneous catalyst for hydrogenated nitrile rubber synthesis
CN119972199B
